Pengaruh Latihan Interval terhadap Kecepatan Lari 100 Meter pada Siswa Kelas VIII SMP Negeri 2 Ampelgading - Tri Mugiarti; Didi Muhtarom; Boby Agustan (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This research was conducted because of the complaints that some students were less enthusiastic about learning about running. (2) Some female students tend to be less active, when they are learning sports they get bored quickly and just sit on the side of the field. (3) The lessons given have not been packaged in modifications so that students are found who are less enthusiastic, bored and lazy to move. (4) Facilities and infrastructure such as balls, there are only two standard balls, one of which is leaky and the other is very hard when kicked. (5) The field used is made of paving. For this reason, the problem formulation can be drawn: How does Interval Training influence the 100 meter running speed of Class VIII students at SMP Negeri 2 Ampelgading? This research method is development research which refers to the development model from Borg & Gall. (1) carry out product analysis to be developed from the results of field observations and literature review. (2) developing the initial product form. (3) expert evaluation using one physical education expert and two junior high school physical education learning experts. (4) small group trials (10 students) using questionnaires and evaluation sheets which were then analyzed. (4) initial product revision. (5) large-scale trial (28 students). (6) revision of the final product after conducting large-scale field trials. (7) final results of the learning development model using interval techniques through revision of large-scale field trials. The data analysis technique uses the percentage description technique.